CANVAS MODEL BUSINESS MEGA BERLIAN JAYA STORE - Zirait, Muh Akif; Herison, Roni; Hardiyono, Hardiyono (Journal of Entrepreneur, Business and Management, 2024)
This study aims to analyze and design the business development strategy of the Mega Berlian Jaya Building Shop using the Business Model Canvas (BMC) approach. This research uses a qualitative method with data collection techniques through observation, interviews, and documentation studies involving store owners, customers, and suppliers. The analysis was carried out by examining nine elements of BMC which include customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. Additionally, SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats that the company faces. The results of the study show that Toko Mega Berlian Jaya has advantages in product quality, relatively affordable prices, and responsive service to customers. However, the limitation of product variety and dependence on fluctuations in the price of building materials are still major challenges. The implementation of the Business Model Canvas helps companies identify opportunities for strategy development, improve operational efficiency, expand partnership networks, and strengthen business competitiveness in a sustainable manner.Keywords: Business Model Canvas, Business Strategy, Building Shop, SWOT Analysis, Business Development